Analisis Pengaruh Kualitas Pelayanan, dan Harga Terhadap Kepuasan Serta Loyalitas Pelanggan pada PT Travel Sasana Lintas Indo - Juleha Safitri; Safna Kurnia Putri; Kustin Hartini; Indra Saputra; Indra Saemona; M. Abrar Habibullah; Hafiz Muhammad Saad (PRODUCTIVITY: Journal of Integrated Business, Management, and Accounting Research, 2025)
This research aims to analyze the influence of service quality and price on customer satisfaction and loyalty at PT Travel Sasana Lintas Indo. The research method uses a quantitative approach with data collection techniques through a questionnaire distributed to the company's customers. The research sample consists of 100 respondents selected using purposive sampling technique. Data analysis was conducted using classical assumption tests and multiple linear regression analysis. The research results show that service quality and price simultaneously have a significant effect on customer satisfaction and loyalty with a contribution of 36% (adjusted R square), while the remaining 64% is influenced by unstudied variables. Partially, service quality has been proven to significantly affect customer satisfaction and loyalty, while the price variable does not show a significant effect when tested separately. These findings indicate that PT Travel Sasana Lintas Indo needs to prioritize improving service quality to maintain and enhance customer satisfaction and loyalty. This research provides managerial implications for the company in developing effective marketing strategies focusing on service quality aspects.